PROJECT-BASED LEARNING IN ENGLISH LANGUAGE TEACHING: DOES IT PROMOTE STUDENTS’ HIGHER-ORDER THINKING SKILLS? - Nurmayasari, Eva; Suciyati Ummu Habibah; Maulidia Rachmawati Nur; Enni Erawati Saragih (ENGLISH, 2025)
ABSTRACT This study explores teachers’ perceptions of Project-Based Learning in English language teaching to promote Higher-Order Thinking Skills. Using a qualitative case study design, the research involved three junior high school teachers in Bogor Regency, selected through purposive sampling. Data was collected via open-ended questionnaires and semi-structured interviews. Findings showed that teachers viewed project-based learning as a student-centered approach emphasizing real-world relevance, collaboration, product creation, and contextual learning. Implementation included planning, scaffolding, group work, facilitation, and feedback. Teachers reported that project-based learning fostered higher-order thinking skills by encouraging critical analysis, creativity, and reflection, although challenges such as time constraints and diverse student abilities remained. The study underscores the need for teacher readiness, resources, and contextualized instruction to optimize project-based learning in promoting higher-order thinking skills. Keywords: Project-Based Learning, Higher-Order Thinking Skills, Teacher Perception, Case Study